Que nous apprennent les « artistes officiels » sur le front de l’intérieur (Home Front) dans la Grande-Bretagne en guerre, 1940-1945 ? - Antoine Capet (Revue LISA)
The notion of Official WarArtists seems to suggest the worst aspects of totalitarian propaganda. The morale-boosting dimension of the work supposedly expected of them seems incompatible with creative freedom―the hallmark of the true artist. The article argues that at first glance the work of people like Edward Ardizzone, Bill Brandt and Henry Moore seems to show that they were a poor choice from the point of view of the authorities, since the morale-boosting aspect of their Home Front scenes was far from obvious at first glance. Indeed the 1942-1943 Exhibition provoked adverse reactions on the part of the visiting public. Yet, it can be argued that fundamentally, at a deeper level, these official artists indirectly praise the indestructibility of British values. Compared with the less subtle propaganda of the Ministry of Information, these works may have been subliminally more convincing―and therefore more valuable for the war effort.